Functionalized Conjugated Polyelectrolytes for Biological Sensing and Imaging. Issue 3 (27th May 2016) - Zhan, Ruoyu; Liu, Bin
Abstract: Conjugated polyelectrolytes (CPEs) are macromolecules with highly delocalized π‐conjugated backbones and charged side chains, which are unique types of active materials, with wide applications in optoelectronics, sensing, imaging, and therapy. By attaching specific groups (e.g., recognition elements, magnetic resonance (MR) contrast agents, gene carriers, and drugs) to the side chain or backbone of CPEs, functionalized CPEs have been developed and used for specific biological applications. In this account, we summarize the recent progress of functionalized CPEs with respect to their synthesis and biomedical applications. Future perspectives are also discussed at the end. Abstract : Functionalized conjugated polyelectrolytes (CPEs) are polymeric materials composed of π‐conjugated backbones, ionic side chains, and functional moieties. They inherit the water‐dispersity, unique optical, biocompatible, and therapeutic properties of CPEs, with specific functionalities for sensing, imaging, and biomedical applications. This account describes the recent progress in the synthesis and applications of functionalized CPEs.